ANALISIS PERAN GURU DALAM PEMBELAJARAN MENGGUNAKAN LOOSE PART UNTUK MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA 5 - 6 TAHUN DI TK SANDHY PUTRA - Putri Andina Siregar; Gita Noveri Eza (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to analyze the role of teachers in learning using loose parts to develop cognitive abilities of children aged 5-6 years at Sandhy Putra Kindergarten. Loose parts are materials that can be moved and used creatively by children in the learning process. This study emphasizes the importance of interaction between teachers and children, as well as how teachers can facilitate children's exploration and imagination through the use of loose parts. The method used in this study is a qualitative approach with observation and documentation as data collection techniques at Sandhy Putra Kindergarten. The results of the study show that teachers have a significant role in creating a conducive learning environment, where children can innovate and explore. Teachers are not only as transmitters of material, but also as facilitators who encourage children to think critically and creatively. This research is expected to contribute to the development of more innovative and effective learning methods in early childhood education, as well as provide insight for educators about the importance of their role in the learning process.